Pro android flash - Chin, Stephen (Apress, 2011)
Did you know you can take your Flash skills beyond the browser, allowing you to make apps for Android, iOS and the BlackBerry Tablet OS? Build dynamic apps today starting with the easy-to-use Android smartphones and tablets. Then, take your app to other platforms without writing native code. Pro Android Flash is the definitive guide to building Flash and other rich Internet applications (RIAs) on the Android platform. It covers the most popular RIA frameworks for Android developers?Flash and Flex?and shows how to build rich, immersive user experiences on both Android smartphones and tablets. You'll learn how to incorporate multimedia, animation, and special effects into your apps for maximum visual appeal. You'll also cover advanced topics, including input methods, hardware inputs, deployment, and performance optimization.